MicroRNAs and Genomic Instability - Huppi, Konrad (2006)
A new species of non-coding RNA, microRNAs (miRNAs) has been identified that may regulate the expression of as many as one third to one half of all protein encoding genes. MicroRNAs are found throughout mammalian genomes, but an association between the location of these miRNAs and regions of genomic instability (or fragile sites) in humans has been suggested [1]. In this review we discuss the possible role of altered miRNA expression on human cancer and conduct an analysis correlating the physical location of murine miRNAs with sites of genetic alteration in mouse models of cancer.